Development of hip displacement in cerebral palsy: a longitudinal register study of 1,045 children - Wagner, Philippe; Hägglund, Gunnar (Acta Orthopaedica, 2022)
Background and purpose — Hip surveillance in children with cerebral palsy (CP) includes repeated radiographic hip examinations and measurements of the hip migration percentage (MP) to identify hips in need of surgery early, to prevent dislocation with the fewest number of radiographic examinations possible. We analyzed the early development of the MP in hips operated on to prevent hip dislocation and hips stabilized without surgery Patients and methods — From the Swedish Surveillance Programme for CP, 5,899 radiographic measurements from 1,045 children with a Gross Motor Function Classification System level III–V born in 1996–2011 were analyzed. For children operated on to prevent hip dislocation, measurements up to the most recent preoperative radiograph were included. The hip with highest MP was analyzed for each child. A mixed-effects model was used to estimate the development of the MP at each age for each child and the population mean. Results — In the 702 children who did not undergo preventive surgery, the mean MP increased with decreasing velocity up to age 6 years. Here it reached 24% (95% confidence interval [CI] 24–25), with a velocity of 0.3%/year (CI 0.0–0.5), remaining approximately stable up to age 12 years. In the 343 children who underwent preventive surgery (219 adductor–psoas lengthening, 124 varus derotation osteotomy of proximal femur), the mean MP increased with an increasing velocity from a mean of 30% (CI 27–32) 3 years before the operation. Interpretation — An increasing rate of hip displacement in hips with an MP > 24% indicates the need for preventive surgery. Hips stabilized without preventive surgery had a decreasing displacement rate and were usually stabilized with an MP < 30% at age 6 years.